2007
DOI: 10.1038/sj.pcan.4500959
|View full text |Cite
|
Sign up to set email alerts
|

Incidental diagnosis of a PSA-negative prostate cancer by 18FDG PET/CT in a patient with hypopharyngeal cancer

Abstract: Diagnosis of prostate cancer (PC) still remains critical as non-invasive screening with prostate specific-antigen (PSA) lacks to indicate malignancy of the prostate in some cases. Recent research has shown that clinically meaningful PC can develop in patients with a PSA value o4 ng/ml, frequently defined as upper limit of normal serum PSA levels. Furthermore, both morphological (computed tomography (CT), magnetic resonance imaging, transrectal ultrasound) and functional imaging with 18 fluorodeoxyglucose posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…No increase in PSA has been detected in a substantial number of prostate cancer patients. Thus, it appears that new biomarkers are needed for the diagnosis and prognosis of patients with prostate cancer …”
Section: Introductionmentioning
confidence: 99%
“…No increase in PSA has been detected in a substantial number of prostate cancer patients. Thus, it appears that new biomarkers are needed for the diagnosis and prognosis of patients with prostate cancer …”
Section: Introductionmentioning
confidence: 99%
“…This biological heterogeneity is reflected in the current perceived mixed experience with FDG-PET in prostate cancer. Animal and preliminary clinical studies have demonstrated that FDG-PET may be useful in the evaluation of patients with high Gleason score primary tumors and serum prostate specific antigen (PSA) levels, in the assessment of the extent of advanced androgen-independent disease, in the detection of metabolically active osseous and soft tissue metastases, and in the assessment of response after androgen ablation and treatment with the novel chemotherapies [722]. Studies have shown that FDG accumulation in both the primary tumor and the metastatic sites decreases in as early as 1–5 months after androgen ablation, which is concordant with the decline in serum PSA level and lesion size on CT [9, 23].…”
Section: Introductionmentioning
confidence: 99%
“…FDG-PET has limited use in diagnosis and staging of clinically organ-confined disease,11 apart from case reports 12 13. FDG-PET might be useful for detecting locally recurrent and/or metastatic disease 14.…”
Section: Discussionmentioning
confidence: 99%